Insight into the genetics of a novel white-striped leaf in rice - Maipoka, Maiporn; Walayaporn, Kitti; Aesomnuk, Wanchana; Ruengphayak, Siriphat; Arikit, Siwaret; Vanavichit, Apichart (Frontiers in Plant Science, 2025)
IntroductionRice is mainly consumed by half of the world’s population. The imminent climate change and population growth expected in the next 30 years will outpace the current rice production capacity, posing risks to food and nutrition security in developing nations. One simplified approach to address this challenge is to improve photosynthetic capacity by increasing chlorophyll content in leaves and stems.MethodologyWe identified a unique white-striped leaf (wsl) mutant, RBR05, which is productive, stage-specific and temperature-sensitive, albeit with low chlorophyll content during the adult stage and recessive to regular solid-green leaf (SGL) rice. We utilised RNA sequencing between the wsl and SGL to identify differentially expressed genes (DEGs) and QTL sequencing to identify genes responsible for the wsl phenotype.ResultWe identified a single recessive gene controlling wsl in RBR05. It is a novel missense mutation (R310H) of OsSAMHD1, a key contributor to the wsl phenotype in RBR05. The mutation, wsl310, turns Arg to His at amino acid position 310 in exon 10, which results in abnormal chloroplast development, a lack of chlorophyll pigment, and the formation of non-chlorophyllous cells in the whitened region of the leaves and leaf sheaths. The wsl310 (qwsl1_503564) was associated with decreased gene expression in the formation of photosynthetic machinery and the chlorophyll biosynthetic pathway, while the upregulation of the OsRNRS1 and genes involved in the expression of plastid-encoded genes was observed. A SNP marker specific for the missense mutation was completely co-segregated with the wsl310 in the segregating population for wsl and SGL, demonstrating that the R310H substitution is responsible for wsl in RBR05.DiscussionPrevious reports have shown that OsSAMHD1 is a hotspot of mutations, which severely affect wsl from the seedling to heading stages. In several events, the interaction between OsRNRS1 and OsSAMHD1 highlights the critical role of maintaining nucleotide homeostasis and proper chloroplast development in compensating for mutations. The functional marker developed in this study will enable rice breeders to further enhance new leaf colouration and productivity in RBR05.